Linking threat maps with management to guide conservation investment. (May 2020) - Tulloch, Vivitskaia J.D.; Turschwell, Mischa P.; Giffin, Alyssa L.; Halpern, Benjamin S.; Connolly, Rod; Griffiths, Laura; Frazer, Melanie; Brown, Christopher J.
Abstract: Stressors to marine ecosystems are increasing, driven by human activities in the sea and on land, and climate change. Cumulative impact maps highlight regions affected by multiple human activities, but efficient conservation investment requires linking dominant pressures to management actions that best address the particular drivers of impacts. We rebuild cumulative impact maps by stressor type (climate change, marine and land) at a global scale to evaluate the expected effectiveness of various management strategies for all coastal territories. Average cumulative impact from non-marine stressors (climate and land) was double those of marine impacts at a national level. The greatest climate impacts by country were in the waters of Pacific Island and Antarctic territories; in the Caspian Sea region and East-Asia for land impacts; and in the waters of European, East-Asian and Caribbean countries for marine impacts. We developed a conservation-effectiveness indicator for the 10 worst-impacted countries in each of the three stressor categories. The indicator considered common management tools for each stressor category: ecosystem-based adaptation and disaster risk reduction (climate), marine protected areas (marine) and integrated coastal management (land). Key disparities were found between broad-scale management of marine ecosystems and the dominant stressors, with existing management in tropical island nations likely insufficient to address intense impacts from climate change. These countries also typically had low performance on governance indicators, suggesting challenges in implementing new mitigation. We highlight trade-offs in making decisions for stressor mitigation and offer strategic guidance on identifying locations to target management of marine, land, or climate impacts.